Optimizing HR Strategy Based on Dave Ulrich's Model to Improve Operational Efficiency in the Transportation Industry - Tiarmin Saragih; Jusuf Roni Siahaan; Raihan Nasywa Nugroho; Aswanti Setyawati; Sarinah Sihombing (Dinasti Publisher, 2025)
The transportation industry faces challenges in improving operational efficiency amid intense competition and regulatory changes. This study aims to analyze the application of the Dave Ulrich model in HR management strategies to improve the operational efficiency of transportation companies. This research uses a qualitative method with a case study approach in a transportation company. Data were collected through in-depth interviews with HR managers and employees, field observations, and document analysis of HR policies. Data analysis was conducted using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. The results showed that an effective HR strategy can improve operational efficiency. Data-driven workforce planning improved resource allocation efficiency by 22%, while industry needs-based training improved employee competencies by 30%. HR digitization through HRIS reduced administrative time by 40%, and the implementation of performance-based incentives increased productivity by 25%. In addition, the retention strategy implemented successfully reduced the turnover rate by 15%. The findings confirm that the integration of HR roles into business strategy through data-driven and technology-driven approaches can improve a company's operational efficiency.